2007
DOI: 10.1111/j.1460-2695.2007.01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Weibull analysis, extrapolations and implications for condition assessment of cast iron water mains

Abstract: The applicability of Weibull statistics to the condition assessment of cast iron water distribution pipes has been considered. The effect of Weibull modulus, characteristic strength, sample size and mode of loading (tension or flexure) on the strength of cast iron water distribution pipes is investigated. The strength distribution of cast iron samples cut from sections of five different water distribution pipes recovered from the ground have been characterized. Strengths have been measured in flexure, at two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(20 citation statements)
references
References 9 publications
2
18
0
Order By: Relevance
“…(A value of 117 GPa is at the upper end of the typical range of 80 to 120 GPa for these materials). Moreover the measured tensile stress at failure for this pipe is consistent with residual strength measurements, and associated Weibull-scaling arguments presented, in previous work on degraded pipe samples (Belmonte et al 2007(Belmonte et al , 2008. Clearly a pipe with a greater degree of degradation will require a smaller temperature difference to trigger fracture.…”
Section: Plain Pipesupporting
confidence: 69%
See 1 more Smart Citation
“…(A value of 117 GPa is at the upper end of the typical range of 80 to 120 GPa for these materials). Moreover the measured tensile stress at failure for this pipe is consistent with residual strength measurements, and associated Weibull-scaling arguments presented, in previous work on degraded pipe samples (Belmonte et al 2007(Belmonte et al , 2008. Clearly a pipe with a greater degree of degradation will require a smaller temperature difference to trigger fracture.…”
Section: Plain Pipesupporting
confidence: 69%
“…A number of researchers have reported on the degradation of strength of cast iron pipes as a result of graphitic corrosion and its relationship to residual performance (Yamamoto et al 1983;Sheikh et al 1990;Conlin and Baker 1991;Rajani and Makar 2000;Atkinson et al 2002;Seica and Packer 2004). In particular, recent studies (Belmonte et al 2007(Belmonte et al , 2008) have used Weibull-based methods to investigate the strengths in tension and flexure of small samples of cast iron extracted from cast iron water distribution pipes. It has been shown that the 5 of 28 strength is degraded significantly as a result of graphitic corrosion in service and…”
Section: Introductionmentioning
confidence: 99%
“…The d c value determined by relation (40) is substantially higher than that in the axial loading case.…”
mentioning
confidence: 60%
“…Further, because of the combination of the size of the pipe and its interaction with the local environment, it is possible to comment on the behaviour of the main a significant distance (multiple casting lengths or 'sticks' of pipe, typically 3-5 m long) either side of a sampling point (Belmonte et al, 2007(Belmonte et al, , 2008(Belmonte et al, , 2009. The size and spread of graphitic corrosion in distribution mains can be seen in Figure 4.…”
Section: Installation Defectsmentioning
confidence: 99%